Frontiers in algorithmics : 8th International Workshop, FAW 2014, Zhangjiajie, China, June 28-30, 2014. Proceedings - Hopcroft, John E.; Wang, Jianxin; Chen, Jianer (Lecture Notes in Computer Science, 2014)
This book constitutes the refereed proceedings of the 8th International Frontiers of Algorithmics Workshop, FAW 2013, held in Zhangjiajie, China, in June 2014. The 30 revised full papers presented together with 2 invited talks were carefully reviewed and selected from 65 submissions. They provide a focused forum on current trends of research on algorithms, discrete structures, operations research, combinatorial optimization and their applications.